Preparation method and application of catalyst for thermal cracking of waste plastics
By using FCC waste catalyst in combination with sodium carbonate and metal oxide precursors, a catalyst with large pore diameter and high pore volume is prepared, which solves the problems of insufficient catalyst activity and low liquid yield in the existing technology, and achieves efficient waste plastics Thermal cracking.
Patent Information
- Application Number
- CN202310887699.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, the catalyst for thermal cracking of waste plastics has a small pore size, low pore volume and insufficient activity, resulting in a low yield of the liquid obtained from catalyzed.
Using FCC waste catalyst as a carrier, combined with sodium carbonate and metal oxide precursors, microspheres are formed through ball milling and beating, followed by acidification, drying and roasting to prepare a catalyst with larger pore size and pore volume.
The activity of the catalyst was increased, the liquid revenue was increased to more than 85%, and the reuse of the FCC waste catalyst was achieved, simplifying the process, and reducing production costs.
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a catalyst for thermal cracking of waste plastics. The catalyst prepared by the method is mainly used in the thermal cracking process of waste plastics. Background Art
[0002] Waste plastics, as part of municipal solid waste, damage environmental hygiene and harm ecosystems. Common disposal methods include landfilling, incineration, and recycling. Landfilling and incineration both cause secondary pollution. Therefore, developing the recycling and resource utilization of waste plastics is a green path to sustainable development.
[0003] Currently, commonly used cracking catalysts include metal oxides and molecular sieves. Traditional metal oxides are low-cost, but their small pore size prevents larger polyolefin molecules from penetrating their inner surface, thus affecting their effective activity. Molecular sieves, especially mesoporous molecular sieve catalysts, have a well-defined pore structure that facilitates the diffusion of large molecules, but their synthesis cost is relatively high.
[0004] CN113976132A uses a fluorosilicic acid solution to expand and reconstruct the catalytic cracking waste equalizer, and then filters and washes it; the filter cake is re-slurried with water, and calcium hydroxide solid is added to react and exchange, filtered, rinsed with barium chloride solution, flash-dried, and then roasted to obtain the finished product. This method has the following disadvantages: (1) fluorine-containing wastewater is generated, and the treatment cost is high; (2) calcium hydroxide solid is added after the pores are expanded, causing partial pore blockage of the catalyst.
[0005] CN113976098A adds calcium chloride and magnesium chloride solutions to a sodium aluminate aqueous solution in parallel, stirs evenly, heats to 60-90°C, ages for 5-10 hours, filters, washes, and roasts; slurries the above materials with water, adds calcium chloride solution for ion exchange, filters, and washes; slurries the filter cake with water, adds silica sol, and sprays to granulate the cake to obtain the finished product. This method has the following disadvantages: (1) the catalyst preparation time is long, the process is complicated, the water consumption is large, and the production cost is high; (2) the catalyst activity is low.
[0006] CN110387471B contacts a spent catalytic cracking catalyst with an alkali-containing mixture and calcines it at 500-1200°C for 0.5-3 hours. The mixture is then mixed with an ammonia source, the pH adjusted to 8.5-11.5, and the reaction is continued for 0.5-5 hours. The treated catalyst is then washed to neutrality to obtain a silicon-aluminum material. This method has the following drawbacks: (1) Utilizing the spent catalytic cracking catalyst requires two treatments to deeply remove nickel and other metals; (2) The pore structure of the silicon-aluminum material is caused by the dissolution of silicon and aluminum in the spent catalytic cracking catalyst, resulting in poor material stability.
[0007] CN108587668A utilizes waste FCC catalysts from oil refining catalytic units, using low-quality heavy oil, waste plastics, and / or mixtures thereof, and subjecting them to high-temperature calcination and modification to remove harmful impurities. The catalyst is then loaded with active components and additives, using the catalyst for cracking, isomerization, desulfurization, pour point reduction, and viscosity reduction under hydrogen or non-hydrogen conditions to produce high-value-added oil and gas products. This method directly loads active components onto the spent FCC catalyst after calcination, but catalyst performance needs to be improved.
[0008] Therefore, there is still a need in this field to study catalysts for thermal cracking of waste plastics. Summary of the Invention
[0009] The main purpose of the present invention is to provide a preparation method and application of a catalyst for the thermal cracking of waste plastics, so as to overcome the defects of the existing catalyst for the thermal cracking of waste plastics, such as small pore size, low pore volume, insufficient activity and low yield of the liquid obtained by catalysis.
[0010] In order to achieve the above object, the present invention provides a method for preparing a catalyst for thermal cracking of waste plastics, comprising the following steps:
[0011] Step 1: mixing the FCC spent catalyst, sodium carbonate and metal oxide precursor to form a powder;
[0012] Step 2, mixing the mixture obtained in step 1, a binder, and water to form microspheres;
[0013] Step 3: acidifying, drying, and calcining the microspheres to obtain a catalyst for thermal cracking of waste plastics.
[0014] In the method for preparing a catalyst for thermal cracking of waste plastics described in the present invention, the metal in the metal oxide precursor is a Group IIA metal or a transition metal.
[0015] In the method for preparing a catalyst for thermal cracking of waste plastics according to the present invention, the metal oxide precursor is selected from at least one of calcium carbonate, magnesium carbonate and zinc carbonate.
[0016] In the method for preparing a catalyst for thermal cracking of waste plastics of the present invention, the mass ratio of the metal oxide precursor, calculated as metal oxide, to the sodium carbonate, the metal oxide precursor and the FCC waste catalyst on a dry basis is 0.01-0.1:0.05-0.2:1.
[0017] In the method for preparing a catalyst for thermal cracking of waste plastics according to the present invention, in step 1, the powder is formed by ball milling, and the ball milling time is 10-20 minutes.
[0018] In the method for preparing a catalyst for thermal cracking of waste plastics of the present invention, the binder is selected from at least one of aluminum sol, neutral silica sol, and acidic silica sol; and the amount of the binder added in step 2 is 2%-10% of the dry basis mass of the FCC waste catalyst.
[0019] In the method for preparing the catalyst for thermal cracking of waste plastics of the present invention, the acidification treatment comprises: immersing the microspheres in an acidic solution.
[0020] In the method for preparing a catalyst for thermal cracking of waste plastics according to the present invention, the acidic solution is an acetic acid solution, and the concentration of the acetic acid solution is 1-4 mol / L.
[0021] The method for preparing a catalyst for thermal cracking of waste plastics of the present invention comprises the following steps: in step 3, the drying temperature is 120-140° C., and the drying time is 2-3 hours; and the roasting temperature is 830-900° C., and the roasting time is 1-3 hours.
[0022] To achieve the above object, the present invention provides the use of the catalyst obtained by the above preparation method in the thermal cracking of waste plastics. The thermal cracking conditions are: cracking temperature 320-450°C, and catalyst addition amount 2wt%-15wt% of the mass of the waste plastics.
[0023] Beneficial effects of the present invention:
[0024] The present invention uses FCC waste catalyst as a carrier and metal oxide as an active component. The original pore structure of the FCC waste catalyst and the CO2 punching effect give the catalyst a larger pore diameter and pore volume, thereby improving the accessibility of the active component. When it is used for the thermal cracking of waste plastics, the liquid yield is greater than 85%.
[0025] The catalyst of the present invention adopts FCC waste catalyst, which not only solves the problem of treating FCC waste catalyst, but also realizes the reuse of FCC waste catalyst, and has simple process and is easy to industrialize. DETAILED DESCRIPTION
[0026] The technical solution of the present invention is described in detail below. The following implementation methods are implemented based on the technical solution of the present invention and provide a detailed implementation process. However, the protection scope of the present invention is not limited to the following implementation methods. In the following implementation methods, structures or experimental methods without specifying specific conditions are generally based on conventional conditions.
[0027] The present invention provides a method for preparing a catalyst for thermal cracking of waste plastics, comprising the following steps:
[0028] Step 1: mixing the FCC spent catalyst, sodium carbonate and metal oxide precursor to form a powder;
[0029] Step 2, mixing the mixture obtained in step 1, a binder, and water to form microspheres;
[0030] Step 3: acidifying, drying, and calcining the microspheres to obtain a catalyst for thermal cracking of waste plastics.
[0031] The present invention uses FCC waste catalyst as a carrier, metal oxide as an active component, and sodium carbonate is added during the catalyst preparation process. The catalyst will have a CO2 punching effect during the calcination process. This, combined with the original pore structure of the FCC waste catalyst, makes the obtained catalyst have a larger pore diameter and pore volume, thereby improving the accessibility of the active components dispersed on the pore surface, promoting the waste plastic conversion efficiency, and making the liquid yield obtained by the catalyst greater than 85%.
[0032] In addition, the ball milling of the FCC waste catalyst and sodium carbonate of the present invention can activate metals, promote the synergistic effect of different metal ions, and help increase the number of reactive atoms, thereby further improving the cracking reaction efficiency of the obtained catalyst.
[0033] In detail, step 1 of the present invention is: mixing FCC waste catalyst, sodium carbonate and metal oxide precursor uniformly to form powder.
[0034] The present invention does not place any particular restrictions on the type of FCC spent catalyst; any catalytic cracking catalyst discarded from a catalytic cracking process may be used. The present invention also does not place any particular restrictions on the structure and element content of the FCC spent catalyst.
[0035] In one embodiment, the metal in the metal oxide precursor of the present invention is a Group IIA metal or a transition metal, such as calcium, magnesium, zinc, etc., and the metal oxide precursor can be a metal carbonate, such as at least one of calcium carbonate, magnesium carbonate, and zinc carbonate.
[0036] The present invention does not specifically limit the method for forming the powder of the mixture of FCC spent catalyst, sodium carbonate, and metal oxide precursor. Preferably, the powder is formed by ball milling, more specifically mechanical ball milling. This activates the metals on the FCC spent catalyst, increases the number of active centers in the resulting catalyst, achieves synergistic effects among different metal ions, realizes resource utilization of the FCC spent catalyst, and further improves the efficiency of the cracking reaction. Furthermore, the present invention uses mechanical ball milling to uniformly disperse the metal oxide precursor on the FCC spent catalyst. After spray forming, the pyrolysis of the metal oxide precursor produces CO2 perforation, resulting in a larger and more uniform pore size in the catalyst. The metal oxide is dispersed on the pore surface, improving active accessibility. In one embodiment, the ball milling time is 10-20 minutes.
[0037] In one embodiment, the mass ratio of the metal oxide precursor, calculated as metal oxide, to the dry weight of the sodium carbonate of the present invention: the metal oxide precursor: 0.01-0.1: 0.05-0.2: 1. In another embodiment, the mass ratio of the sodium carbonate of the present invention: the metal oxide precursor: 0.02-0.05: 0.08-0.15: 1.
[0038] Step 2 of the present invention is: mixing the mixture obtained in step 1, a binder and water to form microspheres.
[0039] The binder of the present invention can be any conventional binder in the art. In one embodiment, the binder of the present invention is selected from a mixture of one or more of alumina sol, neutral silica sol, and acidic silica sol. The binder is added in an amount of 2% to 10% of the dry weight of the spent FCC catalyst.
[0040] The present invention does not particularly limit the amount of water added in step 2, as long as a slurry can be formed. The microspheres can be formed by, for example, spray drying.
[0041] Step 3 of the present invention is: acidifying, drying and roasting the microspheres to obtain a catalyst for thermal cracking of waste plastics.
[0042] In one embodiment, the acidification treatment comprises immersing the microspheres in an acidic solution. The acidic solution may be, for example, acetic acid solution, with a concentration of 1-4 mol / L, for example, 2 mol / L. The immersion method may be equal volume immersion, excess immersion, or the like. Acidification treatment may further improve catalyst activity.
[0043] In one embodiment, the drying temperature in step 3 is 120-140° C., and the drying time is 2-3 hours; the calcination temperature is, for example, 830-900° C., and the calcination time is, for example, 1-3 hours.
[0044] The catalyst prepared by the method of the present invention has a large pore size and pore volume and is suitable as a catalyst for the thermal cracking of waste plastics. In one embodiment, the thermal cracking conditions are: a cracking temperature of 320-450°C, a pressure such as atmospheric pressure, and a catalyst addition amount of 2-15 wt% of the waste plastic mass.
[0045] The present invention does not particularly limit the source of waste plastics. In one embodiment, the waste plastics are a mixture of one or more of waste low-density polyethylene (relative molecular weight of 0.910-0.925), high-density polyethylene (relative molecular weight of 0.941-0.965), polypropylene, and polystyrene.
[0046] The technical solution of the present invention will be described below through specific embodiments.
[0047] Source of raw materials or equipment:
[0048] FCC spent catalyst (specific surface area 113.7m 2 / g, pore volume is 0.127cm 3 / g), sodium carbonate, calcium carbonate, magnesium carbonate, and zinc carbonate were all of analytical grade and produced by Sinopharm Group; alumina sol (Al2O3 19.4 wt%), neutral silica sol (SiO2 30 wt%), acidic silica sol (SiO2 30 wt%), and acetic acid (2 mol / L) were produced by Lanzhou Petrochemical Company.
[0049] Evaluation and analysis methods:
[0050] The pore volume and pore diameter of the catalyst were determined by low-temperature nitrogen adsorption-desorption method (for the analytical method, see "Analytical Methods in Petrochemical Industry (RIPP Experimental Method)", edited by Yang Cuiding et al., Science Press, published in 1990), and the catalyst reaction performance was evaluated using a small fixed bed.
[0051] Example 1
[0052] 536 g of dry FCC waste catalyst, 10.7 g of sodium carbonate, and 161 g of calcium carbonate were mixed evenly, mechanically ball-milled for 12 minutes, then slurried with 42.9 g of aluminum sol and 1531 g of deionized water, and spray-dried to produce microspheres. The sprayed microspheres were impregnated with an equal volume of 2 mol / L acetic acid solution, dried at 125°C for 3 hours, and calcined at 870°C for 1.5 hours to obtain the catalyst C-1 for the thermal cracking of waste plastics, which had an average pore diameter of 9.7 nm and a total pore volume of 0.55 cm 3 / g.
[0053] Using waste plastics as raw materials (polystyrene and polypropylene by mass percentage: 50% and 50%), thermal cracking was carried out at a temperature of 375°C and a catalyst: waste plastics = 5wt% reaction conditions, with a liquid yield of 87.3%.
[0054] Example 2
[0055] 478 g of dry FCC waste catalyst, 14.3 g of sodium carbonate, and 81.3 g of magnesium carbonate were mixed evenly, mechanically ball-milled for 15 minutes, and then mixed with 23.9 g of acidic silica sol and 1365 g of deionized water, slurried, and spray-dried to produce microspheres. The sprayed microspheres were impregnated with an equal volume of 2 mol / L acetic acid solution, dried at 135°C for 2.2 hours, and calcined at 835°C for 2.5 hours to obtain the catalyst C-2 for thermal cracking of waste plastics, which had an average pore diameter of 9.1 nm and a total pore volume of 0.54 cm 3 / g.
[0056] Using waste plastics as raw materials (low-density polyethylene, polystyrene, and polypropylene in mass percentages of 22%, 32%, and 46%), thermal cracking was carried out at a temperature of 410°C and a catalyst: waste plastics ratio of 5.7wt%, with a liquid yield of 86.8%.
[0057] Example 3
[0058] 603 g of dry FCC waste catalyst, 6.1 g of sodium carbonate, and 121 g of zinc carbonate were mixed evenly, mechanically ball-milled for 19 minutes, then slurried with 42.3 g of neutral silica sol and 2010 g of deionized water, and spray-dried to produce microspheres. The sprayed microspheres were impregnated with an equal volume of 2 mol / L acetic acid solution, dried at 130°C for 2 hours, and calcined at 895°C for 1.1 hours to obtain the catalyst C-3 for the thermal cracking of waste plastics, which had an average pore diameter of 8.6 nm and a total pore volume of 0.57 cm 3 / g.
[0059] Using waste plastics as raw materials (low-density polyethylene, high-density polyethylene, polypropylene, polystyrene mass percentage: 20%, 18%, 46%, 16%), thermal cracking was carried out at a temperature of 405°C and a catalyst: waste plastics = 9wt% reaction conditions, with a liquid yield of 87.9%.
[0060] Example 4
[0061] 712 g of dry FCC waste catalyst, 35.6 g of sodium carbonate, 57 g of zinc carbonate, and 57 g of calcium carbonate were mixed evenly and mechanically ball-milled for 11 minutes. The mixture was then slurried with 14.3 g of neutral silica sol, 21.4 g of acidic silica sol, and 2373 g of deionized water, and spray-dried to produce microspheres. The sprayed microspheres were impregnated with an equal volume of 2 mol / L acetic acid solution, dried at 122°C for 2.4 hours, and calcined at 850°C for 2 hours to obtain the catalyst C-4 for the thermal cracking of waste plastics, which had an average pore diameter of 9.0 nm and a total pore volume of 0.61 cm 3 / g.
[0062] Using waste polypropylene as raw material, thermal cracking was carried out at a temperature of 365°C and a catalyst:polypropylene ratio of 9.0wt%, with a liquid yield of 88.1%.
[0063] Example 5
[0064] 399g of dry FCC waste catalyst, 16g of sodium carbonate, 79.8g of magnesium carbonate, and 43.9g of calcium carbonate were mixed evenly and mechanically ball-milled for 15 minutes. The mixture was then slurried with 11.9g of aluminum sol, 15.9g of acidic silica sol, and 1330g of deionized water, and spray-dried to produce microspheres. The sprayed microspheres were impregnated with an equal volume of 2mol / L acetic acid solution, dried at 138°C for 2.7 hours, and calcined at 880°C for 1 hour to obtain the catalyst C-5 for the thermal cracking of waste plastics. The catalyst had an average pore diameter of 8.6nm and a total pore volume of 0.56cm 3 / g.
[0065] Using waste plastics as raw materials (polystyrene and polypropylene by mass percentage: 60% and 40%), thermal cracking was carried out at a temperature of 395°C and a catalyst: waste plastics = 4.5wt% reaction conditions, with a liquid yield of 87.1%.
[0066] Example 6
[0067] 812g of dry FCC waste catalyst, 24g of sodium carbonate, 113g of magnesium carbonate, and 48.7g of zinc carbonate were mixed evenly, mechanically ball-milled for 10 minutes, and then slurried with 8.2g of aluminum sol, 16.3g of neutral silica sol, and 2703g of deionized water, and spray-dried to produce microspheres. The sprayed microspheres were impregnated with an equal volume of 2mol / L acetic acid solution, dried at 128°C for 2.5 hours, and calcined at 840°C for 2.4 hours to obtain the catalyst C-6 for the thermal cracking of waste plastics, which had an average pore diameter of 9.7nm and a total pore volume of 0.63cm 3 / g.
[0068] Using waste plastics as raw materials (low-density polyethylene and polypropylene by mass percentage: 50% and 50%), thermal cracking was carried out at a temperature of 370°C and a catalyst: waste plastics = 5.5wt% reaction conditions, with a liquid yield of 89.3%.
[0069] Example 7
[0070] 567 g of dry FCC waste catalyst, 28 g of sodium carbonate, 45 g of calcium carbonate, 23 g of magnesium carbonate, and 34 g of zinc carbonate were mixed evenly, mechanically ball-milled for 16 minutes, and then mixed with 17 g of aluminum sol and 2703 g of deionized water, beaten into a slurry, and spray-dried to produce microspheres. The sprayed microspheres were impregnated with an equal volume of 2 mol / L acetic acid solution, dried at 135°C for 2 hours, and calcined at 860°C for 2.2 hours to obtain the catalyst C-7 for the thermal cracking of waste plastics, which had an average pore diameter of 10.1 nm and a total pore volume of 0.64 cm 3 / g.
[0071] Waste polystyrene was used as raw material and thermal cracking was carried out at a temperature of 340°C and a catalyst C-7:waste polystyrene ratio of 6 wt %, with a liquid yield of 96.8%.
[0072] Example 8
[0073] 496g of dry FCC waste catalyst, 19g of sodium carbonate, and 148g of magnesium carbonate were mixed evenly and mechanically ball-milled for 18 minutes. The mixture was then slurried with 9.9g of aluminum sol, 14.8g of neutral silica sol, 19.8g of acidic silica sol, and 2703g of deionized water, and spray-dried to produce microspheres. The sprayed microspheres were impregnated with an equal volume of 2mol / L acetic acid solution, dried at 130°C for 2.5 hours, and calcined at 850°C for 2 hours to obtain the catalyst C-8 for thermal cracking of waste plastics. The catalyst had an average pore diameter of 8.9nm and a total pore volume of 0.57cm 3 / g.
[0074] Using waste plastics as raw materials (low-density polyethylene and high-density polyethylene mass percentage: 20% and 80%), thermal cracking was carried out at a temperature of 440°C and a catalyst: waste plastics = 8wt% reaction conditions, with a liquid yield of 86.1%.
[0075] Example 9
[0076] 635g of dry FCC waste catalyst, 12.7g of sodium carbonate, and 88.9g of calcium carbonate were mixed evenly, mechanically ball-milled for 15 minutes, and then mixed with 31.8g of acidic silica sol and 2110g of deionized water, slurried, and spray-dried to produce microspheres. The sprayed microspheres were impregnated with an equal volume of 2mol / L acetic acid solution, dried at 125°C for 2 hours, and calcined at 870°C for 1.5 hours to obtain the catalyst C-9 for thermal cracking of waste plastics, which had an average pore diameter of 9.3nm and a total pore volume of 0.56cm 3 / g.
[0077] Using waste plastics as raw materials (polystyrene and low-density polyethylene by mass percentage: 80% and 20%), thermal cracking was carried out at a temperature of 375°C and a catalyst: waste plastics = 7wt% reaction conditions, with a liquid yield of 90.1%.
[0078] Example 10
[0079] 563 g of dry FCC waste catalyst, 22.5 g of sodium carbonate, 90 g of magnesium carbonate, and 61 g of zinc carbonate were mixed evenly and mechanically ball-milled for 13 minutes. The mixture was then slurried with 11.3 g of aluminum sol, 28 g of acidic silica sol, and 1870 g of deionized water, and spray-dried to produce microspheres. The sprayed microspheres were impregnated with an equal volume of 2 mol / L acetic acid solution, dried at 130°C for 2.9 hours, and calcined at 855°C for 2 hours to obtain the catalyst C-10 for the thermal cracking of waste plastics. The catalyst had an average pore diameter of 9.1 nm and a total pore volume of 0.59 cm 3 / g.
[0080] Using waste plastics as raw materials (low-density polyethylene and polypropylene by mass percentage: 20% and 80%), thermal cracking was carried out at a temperature of 400°C and a catalyst: waste plastics = 3wt% reaction conditions, with a liquid yield of 86.7%.
[0081] Comparative Example 1
[0082] 536g of dry FCC waste catalyst and 10.7g of sodium carbonate were mixed evenly, mechanically ball-milled for 12 minutes, then slurried with 42.9g of aluminum sol and 1531g of deionized water, and spray-dried to produce microspheres. The sprayed microspheres were impregnated with an equal volume of 2mol / L acetic acid solution, dried at 125°C for 3 hours, and calcined at 870°C for 1.5 hours to obtain catalyst D-1 for the thermal cracking of waste plastics. Its average pore diameter was 7.3nm and its total pore volume was 0.43cm 3 / g.
[0083] Using waste plastics as raw materials (polystyrene and polypropylene by mass percentage: 50% and 50%), thermal cracking was carried out at a temperature of 375°C and a catalyst: waste plastics = 5wt% reaction conditions, with a liquid yield of 81.6%.
[0084] Comparative Example 2
[0085] 478g of dry FCC waste catalyst and 81.3g of magnesium carbonate were mixed evenly, mechanically ball-milled for 15 minutes, then slurried with 23.9g of acidic silica sol and 1365g of deionized water, and spray-dried to form microspheres. The sprayed microspheres were impregnated with an equal volume of 2mol / L acetic acid solution, dried at 135°C for 2.2 hours, and calcined at 835°C for 2.5 hours to obtain catalyst D-2 for the thermal cracking of waste plastics. Its average pore diameter was 7.6nm and its total pore volume was 0.47cm 3 / g.
[0086] Using waste plastics as raw materials (low-density polyethylene, polystyrene, and polypropylene in mass percentages of 20%, 32%, and 46%), thermal cracking was carried out at a temperature of 410°C and a catalyst: waste plastics ratio of 5.7wt%, with a liquid yield of 83.3%.
[0087] Comparative Example 3
[0088] 536 g of dry FCC waste catalyst was calcined at 870 °C for 1.5 hours to obtain catalyst D-3 for thermal cracking of waste plastics. The catalyst had an average pore diameter of 6.1 nm and a total pore volume of 0.13 cm 3 / g. Using waste plastics as raw materials (polystyrene, polypropylene: 50%, 50%), thermal cracking was carried out at a temperature of 375°C and a catalyst: waste plastics = 5wt% reaction conditions, with a liquid yield of 73.4%.
[0089] As shown in the above examples and comparative examples, the catalyst prepared by the method of the present invention has a larger pore diameter and pore volume, uses metal oxide as an active component, is used to catalyze the thermal cracking of waste plastics, and has a higher liquid yield.
[0090] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a catalyst for thermal cracking of waste plastics, characterized in that: The steps include: Step 1, mixing FCC waste catalyst, sodium carbonate and metal oxide precursor uniformly to form powder; Step 2, mixing the mixture obtained in step 1, a binder, and water to form microspheres; Step 3, acidifying, drying and calcining the microspheres to obtain a catalyst for thermal cracking of waste plastics.
2. The method for preparing a catalyst for thermal cracking of waste plastics according to claim 1, characterized in that: The metal in the metal oxide precursor is a Group IIA metal or a transition metal.
3. The method for preparing a catalyst for thermal cracking of waste plastics according to claim 2, characterized in that: The metal oxide precursor is selected from at least one of calcium carbonate, magnesium carbonate and zinc carbonate.
4. The method for preparing a catalyst for thermal cracking of waste plastics according to claim 1, characterized in that: The metal oxide precursor is calculated as metal oxide, and the mass ratio of the sodium carbonate, the metal oxide precursor and the FCC waste catalyst on a dry basis is: 0.01-0.1:0.05-0.2:
1.
5. The method for preparing a catalyst for thermal cracking of waste plastics according to claim 1, characterized in that: In step 1, the powder is formed by ball milling, and the ball milling time is 10-20 minutes.
6. The method for preparing a catalyst for thermal cracking of waste plastics according to claim 1, characterized in that: The binder is selected from at least one of aluminum sol, neutral silica sol and acidic silica sol; the amount of the binder added in step 2 is 2%-10% of the dry basis weight of the FCC waste catalyst.
7. The method for preparing a catalyst for thermal cracking of waste plastics according to claim 1, characterized in that: The acidification treatment is: immersing the microspheres in an acidic solution.
8. The method for preparing a catalyst for thermal cracking of waste plastics according to claim 7, characterized in that: The acidic solution is an acetic acid solution, and the concentration of the acetic acid solution is 1-4 mol / L.
9. The method for preparing a catalyst for thermal cracking of waste plastics according to claim 1, characterized in that: In step 3, the drying temperature is 120-140° C., and the drying time is 2-3 hours; the roasting temperature is 830-900° C., and the roasting time is 1-3 hours.
10. Use of the catalyst obtained by the preparation method according to any one of claims 1 to 9 in thermal cracking of waste plastics, characterized in that: The conditions for thermal cracking are: cracking temperature 320-450°C, and the amount of catalyst added is 2wt%-15wt% of the mass of the waste plastics.
Citation Information
Patent Citations
Method for producing light oil gas by pyrolysis desulfurization and visbreaking of inferior heavy oil and waste plastics
CN108587668A
Deep nickel removal method of spent catalytic cracking catalyst and the resulting silicon-aluminum materials and their applications
CN110387471B
Preparation method of alkaline catalyst for thermal cracking of waste plastics
CN113976098A
Preparation method of basic catalyst for thermal cracking of waste plastics
CN113976132A
Method for preparing microsphere FCC (fluid catalytic cracking) catalyst
CN104549551A